Simultaneous appearance of two malignant neoplasias in a 25 year-old woman. A case presentation. - Miryam González González del Pino; Mayrim Hernández González (Medisur)
Lung cancer and cervix uterine cancer appear in an independent way in women worldwide and both are frequently on them. However, these neoplasias are rarely presented in association. In the medical reviewed literature this association with a primary character has not been found. Thus, a 25 year-old woman who was diagnosed with both diseases is the case we would like to present to you.